1997
DOI: 10.1089/lap.1997.7.37
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Metallic Clips Used During Laparoscopic Cholecystectomy and Formation of Gallstones Around Them: Surgical Implications from a Prospective Study

Abstract: Two groups of patients, with laparoscopic cholecystectomy (LC) were prospectively studied. All patients had serial plain abdominal X-ray examinations at various intervals after operation, to record the position of clips placed during LC. Seventy-one patients had less cystic duct (CD) dissection and > or =4 clips placed during the procedure. One hundred and fifteen patients had a larger CD dissection and only 4 clips placed (2 on the cystic artery and 2 on the CD, without additional clips on smaller vessels). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Seven of the reported cases had spontaneous clips/stones migrations either after failed ERCP extractions or after LC. 20,29,33,36,38,63,69 All had ES done during ERCP. Therefore, the routine use of precholecystectomy ERCP with ES may be an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the reported cases had spontaneous clips/stones migrations either after failed ERCP extractions or after LC. 20,29,33,36,38,63,69 All had ES done during ERCP. Therefore, the routine use of precholecystectomy ERCP with ES may be an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Metallic clips also can migrate. Cetta et al [2] reported that clip migration occurred in18 of 71 patients with four or more metal clips over the course of 1 year. Clips migrated at regular intervals from their initial site to either the peritoneal cavity or the common bile duct, serving as a potential nidus for gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, absorbable material can also act as a nucleus for subsequent bile duct stone formation until it is absorbed [5,18]. In the case of laparoscopic cholecystectomy, Jain et al have recommended the use of an ultrasonically activated scalpel instead of clips to decrease the chances of morbidity [19].…”
Section: Discussionmentioning
confidence: 99%